Socialization and Education on Hydrogel Nanokitosan from Belut Sawah (Monopterus albus) Extract as a Future Anti-Aging Candidate (JURNAL PENGMAS KESTRA (JPK), 2025)
Background: Premature aging is a serious problem, especially among women. The aging process can occur at any time and progress rapidly. This condition may be caused by exposure to sunlight radiation, which induces the formation of Reactive Oxygen Species (ROS) in the skin. When ROS levels exceed the antioxidant defense capacity of skin cells, it can lead to dry, thin, inelastic, and wrinkled skin, and even skin cancer. Antioxidants are compounds that can neutralize and slow oxidative reactions, thereby inhibiting premature aging. Belut sawah (Monopterus albus) is commonly consumed by the community as a food source. Previous studies have reported that rice field eel extract has been used to treat incision wounds, gastric ulcers, and anemia. Rice field eel contains vitamin A, vitamin B, and selenium, and is widely found in rice fields and muddy ponds in the Lubuk Pakam area. Formulating the extract in nanokitosan derived from shrimp shells has been reported to provide better delivery of antioxidant effects into the skin layers. Objective: To provide socialization and education on the utilization of hydrogel preparations as future anti-aging candidates that are more acceptable to the community. Methods: The method involved direct socialization activities conducted among pharmacy students of the Medistra Institute of Health, Lubuk Pakam. Data were collected using questionnaires with a pre-test and post-test design. Results: The hydrogel was formulated from rice field eel extract at various concentrations and had undergone laboratory testing. The results showed that the nanokitosan hydrogel of rice field eel extract was not only dermatologically safe but also had high potential for consumer acceptance, making it suitable for further development as a natural-based anti-aging product. These results were presented to participants, who answered each item in the questionnaire. The level of understanding after socialization showed that 90% of students understood the benefits of nanogel preparations of Belut sawah (Monopterus albus) extract for wound healing. The indicator of success for this socialization activity was that more than 80% of students correctly completed the questionnaire with scores above 75. Conclusion: Formula III with a concentration of 7.5% is recommended as the best dose for wound treatment, as it meets the standards for formulation evaluation and effectiveness testing. Pharmacy students demonstrated understanding and the ability to conduct further research on anti-aging at the biomolecular level.